2017
DOI: 10.1007/s10549-017-4449-4
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity modify the relationship between physical activity and breast cancer risk?

Abstract: The results of this meta-analysis suggest that physical activity is associated with a larger breast cancer risk reduction among women who are normal weight or overweight than among women who are obese. Since the included studies used diverse methods for assessment of physical activity and categories of BMI, results should be interpreted with caution and additional work is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[27][28][29] A recent meta-analysis of 18 cohort and 11 case-control studies found that self-reported physical activity was associated with the greatest magnitude reduction in breast cancer risk among women with lower BMI, and that there was no significant association between self-reported physical activity and breast cancer risk among women who were obese. 5 One factor that may partly explain the lack of risk reduction associated with physical activity in some studies is the over-reporting of physical activity among individuals with higher BMI. 30 In our analyses, the decreased risk associated with physical activity did not appear to vary by BMI and this lack of variation in association with BMI is consistent with that from a recent study that pooled data from 10 prospective cohorts with self-reported physical activity as the exposure and incident breast cancer as the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] A recent meta-analysis of 18 cohort and 11 case-control studies found that self-reported physical activity was associated with the greatest magnitude reduction in breast cancer risk among women with lower BMI, and that there was no significant association between self-reported physical activity and breast cancer risk among women who were obese. 5 One factor that may partly explain the lack of risk reduction associated with physical activity in some studies is the over-reporting of physical activity among individuals with higher BMI. 30 In our analyses, the decreased risk associated with physical activity did not appear to vary by BMI and this lack of variation in association with BMI is consistent with that from a recent study that pooled data from 10 prospective cohorts with self-reported physical activity as the exposure and incident breast cancer as the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also reported greater reductions in risk associated with physical activity among postmenopausal women 1 and those with a relatively low body mass index (BMI), 5 but it is unclear as to what extent these observed differences may be attributed to differential reporting bias in self-reported estimates of physical activity by subgroups of menopausal status and BMI, as opposed to genuine effect modification.…”
Section: Introductionmentioning
confidence: 99%
“…(6) The updated search identified two meta-analyses on the associations between physical activity and breast cancer risk, both of which reported reduced breast cancer risk comparing high versus low levels of physical activity for the total population, (12,13) although one meta-analysis found no association of physical activity with breast cancer occurring before menopause. (12) The updated search identified five publications of cohort studies (14-18) that investigated the associations of physical activity with breast cancer risk. One cohort study observed that strenuous activity was inversely and significantly associated with reduced breast cancer risk, particularly in certain molecular subtypes.…”
Section: Cancer Primary Preventionmentioning
confidence: 99%
“…In addition, physical activity reduces circulating leptin and insulin levels, and insulin resistance while increasing adiponectin, IGFBP-1 and IGFBP-3 levels (19)(20)(21). These influence the associations between the insulin pathway and breast cancer development and progression (11,16,17,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%